LEGAL POLITICS CHILD PROTECTION BASED ON LAW NO. 1 YEAR 2023 ON THE CRIMINAL CODE - Arhanda Putra, Alif; Adyastari Cahyani (Fakultas Hukum, Universitas Samudra, 2024)
The formulation and drafting of Law Number 1 Year 2023 on the Criminal Code (hereinafter referred to as KUHP) is intended to replace the Wetboek van Strafrecht or the Criminal Code as stipulated by Law Number 1 Year 1946 on Criminal Law Regulations which has been amended several times. The effort is carried out in a directed, integrated, and planned manner so that it can support national development in various fields in accordance with the demands of development as well as the level of legal awareness and dynamics that develop in society. Child protection is based on Law Number 1 of 2023 concerning the Criminal Code which stipulates that criminal responsibility cannot be imposed on children who at the time of committing a criminal offense were not yet 12 (twelve) years old, which is an excuse. As well as considering the provisions referred to in Article 51 through Article 54, imprisonment should not be imposed if it is found that the defendant is a child. This research uses the type and type of normative legal research that examines and analyzes legal theories, legal principles and things written in legislation (law in book) and legal literature to answer problem issues. The research method uses a statutory approach (The Statue Approach) and a conceptual approach (The Conceptual Approach). The legal material collection technique used is a literature study document study. The legal materials that have been collected are then processed and analyzed prescriptively with deductive method. Thus, the politics of criminal law underlying the criminal law reform process involves policies in determining whether an act should be considered a violation of the law (criminalization) or not (decriminalization). One important aspect of community protection is the protection of victims and efforts to restore disturbed values in the community. Legal protection is manifested in the presence of various laws and regulations. The forms of protection or categories vary, examples of legal protection include civil law protection, consumer law protection, child protection, and so on